Endoscopic Management of Portal Hypertension - Said A. Al-Busafi; Peter Ghali; Philip Wong; Marc Deschenes (International Journal of Hepatology)
Cirrhosis is the leading cause of portal hypertension worldwide, with the development of bleeding gastroesophageal varices being one of the most life-threatening consequences. Endoscopy plays an indispensible role in the diagnosis, staging, and prophylactic or active management of varices. With the expected future refinements in endoscopic technology, capsule endoscopy may one day replace traditional gastroscopy as a diagnostic modality, whereas endoscopic ultrasound may more precisely guide interventional therapy for gastric varices.